2008
DOI: 10.1002/pssc.200778549
|View full text |Cite
|
Sign up to set email alerts
|

InN/In2O3 heterostructures

Abstract: Cubic (c‐) InN is predicted to possess superior electronic properties for device applications, while c‐In2O3 is an excellent candidate as gate material for InN based high‐frequency field effect transistors. In this paper, the epitaxial growth of the InN/In2O3 and In2O3/InN heterosystems was investigated. High‐quality c‐InN (001) was deposited on (001) In2O3 tem‐ plate, while single crystalline c‐In2O3 was epitaxially grown on hexagonal InN (0001). The epitaxial relationship of the heterosystems was determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This is a puzzling result because the [1̅1̅0] direction is not orthogonal to [111]. The result is also at variance with the work of Ambacher and co-workers, who have made extensive studies of the growth of In 2 O 3 on Al 2 O 3 (0001) by MOCVD using In­(CH 3 ) 3 and H 2 O as precursors. At high flow rates of the In­(CH 3 ) 3 precursor and at low substrate temperatures the bcc polymorph of In 2 O 3 grows with (001) orientation, giving the out of plane epitaxial relationship bcc -In 2 O 3 [001]∥Al 2 O 3 [0001]. This is a surprising result as the (001) surface of In 2 O 3 is a polar Tasker type III surface with a higher surface energy than the quadrupolar (111) surface. , In-plane, the films were found to be built up from square or rectangular domains rotated by 30° relative to each other with bcc -In 2 O 3 [11̅0]∥Al 2 O 3 [112̅0], etc. However, at higher temperatures and lower flow rates a biphasic mixture of bcc- and rh -In 2 O 3 was obtained: phase pure rh -In 2 O 3 (0001) could be grown at 600 °C with very low In­(CH 3 ) 3 flow rates of around 4 μmol/min. ,, Simple epitaxy with rh -In 2 O 3 [0001]∥Al 2 O 3 [0001] and rh -In 2 O 3 [101̅0]∥A1 2 O 3 [101̅0] was observed.…”
Section: Introductionmentioning
confidence: 93%
“…This is a puzzling result because the [1̅1̅0] direction is not orthogonal to [111]. The result is also at variance with the work of Ambacher and co-workers, who have made extensive studies of the growth of In 2 O 3 on Al 2 O 3 (0001) by MOCVD using In­(CH 3 ) 3 and H 2 O as precursors. At high flow rates of the In­(CH 3 ) 3 precursor and at low substrate temperatures the bcc polymorph of In 2 O 3 grows with (001) orientation, giving the out of plane epitaxial relationship bcc -In 2 O 3 [001]∥Al 2 O 3 [0001]. This is a surprising result as the (001) surface of In 2 O 3 is a polar Tasker type III surface with a higher surface energy than the quadrupolar (111) surface. , In-plane, the films were found to be built up from square or rectangular domains rotated by 30° relative to each other with bcc -In 2 O 3 [11̅0]∥Al 2 O 3 [112̅0], etc. However, at higher temperatures and lower flow rates a biphasic mixture of bcc- and rh -In 2 O 3 was obtained: phase pure rh -In 2 O 3 (0001) could be grown at 600 °C with very low In­(CH 3 ) 3 flow rates of around 4 μmol/min. ,, Simple epitaxy with rh -In 2 O 3 [0001]∥Al 2 O 3 [0001] and rh -In 2 O 3 [101̅0]∥A1 2 O 3 [101̅0] was observed.…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that after the initial growth of InN and subsequent formation of oxynitride, a mixed crystalline phase of In 2 O 3 and InN crystals was grown after a short annealing time (10 min) at 550°C [ 35 ]. The cubic In 2 O 3 phase was formed layer-by-layer, after subsequent oxidization of the hexagonal InN layers [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In related reports, the growth of cubic (001) InN films on (001) In 2 O 3 buffer layers was described. [4][5][6] On the other hand, Song et al reported the band offset of InN/In 2 O 3 heterojunctions, 7) and Shih et al reported the disappearance of pin holes in InN grown on a ZnO substrate caused by the existence of the In 2 O 3 layer formed by an In/ZnO reaction. 8) However, there have been no concrete experimental data about the effects of the (111) In 2 O 3 underlayer on the crystallinity of hexagonal (0001) InN and InGaN thin films grown on c-face sapphire substrates.…”
mentioning
confidence: 96%